Rural household resilience to food insecurity in Mekiet district, Ethiopia - Dessie, Tadsual Asfaw; Demsie, Birhan Sisay (Frontiers in Sustainable Food Systems, 2024)
Now food insecurity is a global agenda in the world and a top national agenda in Ethiopia.However, food insecurity is still a serious issue at present time in rural Ethiopia. Therefore, this study investigated household resilience to food insecurity in rural residents of Mekiet District.Cross sectional research design was conducted in two agro ecological zones of Mekiet district from lowland and midland involving 228 respondents. The study employed quantitative and qualitative approach. Multi-stage sampling techniques were employed to select sample households. Factor analysis was employed to analyze the data. The result from factor analysis using TANGO approach showed that the latent variables of absorptive and adaptive capacity have a load of 0.98 and 0.79 respectively. On the other hand, transformative capacity is found to be a negative load (-0.78), all variables are found to be statistically significant. The mean household resilience capacity index is 0.51.The variables of absorptive and adaptive capacities are positively associated with household resilience capacity. In contrast, transformative capacity is found to be a strong negative load. All those loads are significant with absolute value of factor loadings greater than 0.364 which is recommended for sample size of 200 and above. Those variables are also highly correlated with resilience capacity. The study recommends, resilience programs should be implementing at district, community, and households levels to enhance resilience to food insecurity.